Attitudes Toward Psychological Disorders and Alternative Medicine in Saudi Participants - Alegiry, Mohamed H.; Hajrah, Nahid H.; Alzahrani, Nada A. Y; Shawki, Hossam H.; Khan, Muhammadh; Zrelli, Houda; Atef, Ahmed; Kim, Youngil; Alsafari, Ibrahim A.; Arfaoui, Leila; Alharby, Hesham F.; Hajar, Abdulrahman S.; et al. (Frontiers in Psychiatry, 2021)
Background: This study was designed to investigate Saudis’ attitudes toward mental distress and psychotropic medication, attribution of causes, expected side effects and to analyse participants’s expectations toward alternative or complementary medicine using aromatic and medicinal plants, through a survey. Method: The study included 664 participants (citizen and residents in Saudi Arabia) who were randomly contacted via email and social media and gave their consent to completed a questionnaire dealing with 39 items that can be clustered in six parts. Descriptive statistics and Chi-square for cross-tabulation were generated using SPSS. Results: Among 664 participants, 73.4% believed that there are some positive and negative outcomes of psychotropic medication. Participants (72.0%) think that the most important reason leading to psychological disorders is mainly due to the loss of a relative or beloved person, and 73.9% considered psychic session as one of the possible treatments of psychological disorders. Surprisingly, only 18.8% of the participants agreed that medicinal and aromatic plants could be a possible treatment of the psychological disorder. Participants (82 %) consider that physicians are the most trustful and preferred source of information about altermative and complementary medicine.